Efficacy and Acceptance of a Lombard-response Device for Hypophonia in Parkinson's Disease. (11th September 2020) - Adams, Scott; Kumar, Niraj; Rizek, Philippe; Hong, Angeline; Zhang, Jenny; Senthinathan, Anita; Mancinelli, Cynthia; Knowles, Thea; Jog, Mandar
ABSTRACT: Objective: The purpose of this study was to examine the effectiveness, satisfaction, and acceptance of a low-cost Lombard-response (LR) device in a group of individuals with Parkinson's disease (IWPD) and their communication partners (CPs). Method: Sixteen IWPD and hypophonia and their CPs participated in the study. The IWPD wore a LR device that included a small MP3 player (Sony Walkman) and headphones playing a multi-talker noise audio file at 80 dB during lab-based speech tasks and during their daily conversational speech over a 2-week device trial period. Outcome measures included average conversational speech intensity and scores on a questionnaire related to speech impairment, communication effectiveness, and device satisfaction. Results: Conversational speech intensity of the IWPD is increased by 7 to 10 dB with the LR device. Following a 2-week trial period, eight of the IWPD (50%) gave the LR device moderate-to-high satisfaction and effectiveness ratings and decided to purchase the device for long-term daily use. At the 4-month follow-up, none of the IWPDs were still using the LR device. Device rejection was related to discomfort (loudness), headaches, interference with cognition, and difficulty controlling device. Conclusion: Short-term acceptance and satisfaction with the LR device was moderate, but long-term acceptance, beyond 4 months, was absent. Future studies are required to determine if other types of low-cost LR devices can be developed that improve long-term efficacy and device acceptance in IWPD and hypophonia.